Self-Regulated Learning sebagai Prediktor Kemandirian Belajar Siswa di Era Digital: Studi Kasus di MTs Hidayatul Muhajirin Palangka Raya - Maulida Sari; Surawan Surawan (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to analyze the role of Self-Regulated Learning (SRL) as a predictor of student learning independence in the digital era, with a case study focus at Mts Hidayadul Muhajirin Palangka Raya. The digital era requires students to be able to learn independently, adaptively, and be responsible for their learning process. SRL, which includes aspects of motivation, cognitive strategies, and self-management, is one of the important factors that can affect the level of student learning independence. This research uses a qualitative approach with data collection techniques using observation and interviews. The data were analyzed to obtain research findings. The subjects in this study were Hidayatul Muhajirin Palangka Raya Mts students who had low SRL, but there were also some students who had high SRL. Self-Regulates Learning in these students is independently influenced by several factors, namely 1) self-confidence, 2) internal motivation, 3) direct support from the family while the inhibiting factors are 1) the absence of encouragement from parents to tell their children to study, 2) getting used to the comfort zone.